PENYULUHAN BIMBINGAN REMAJA USIA SEKOLAH SEBAGAI UPAYA PREVENTIF DALAM MENEKAN ANGKA PERNIKAHAN DINI DI PEDESAAN - Ali, Ahmad Zulfikar; Anam, Saiful; Salimin, Salimin (Universitas Al-Amien Prenduan, 2024)
Early marriage remains a significant social problem in rural areas, mainly due to low awareness among adolescents of the importance of education, psychological maturity, and economic readiness before marriage. This community service activity aims to provide counseling and guidance to school-age adolescents through the School-Age Adolescent Guidance (BRUS) program as a preventive measure to reduce the rate of early marriage. The implementation method is carried out through a participatory approach with stages of socialization, interactive counseling, group discussions, and psychosocial assistance. The counseling material covers healthy reproductive education, character building, motivation to continue education, and productive future planning. The results of the activity showed an increase in adolescents' understanding of the negative impacts of early marriage and a growing awareness to delay marriage until they reach the ideal maturity. Additionally, support from schools, parents, and community leaders is a crucial factor in the sustainability of the BRUS program. This initiative is expected to create a supportive social environment for adolescents to develop optimally without the burden of early marriage, thereby contributing to the improvement of human resource quality in rural areas.